2022
DOI: 10.1155/2022/7820017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Carbohydrate Levels on Growth Performance, Body Composition, Antioxidant Capacity, Immunity, and Liver Morphology in Oncorhynchus mykiss under Cage Culture with Flowing Freshwater

Abstract: The purpose of this study is to investigate the effects of dietary carbohydrate levels on growth performance, body composition, antioxidant capacity, immunity, and liver morphology in Oncorhynchus mykiss under cage culture with flowing freshwater. Fish (initial body weight 25.70 ± 0.24 g) were fed five isonitrogenous (420 g/kg protein) and isolipidic (150 g/kg lipid) diets containing 50.6, 102.1, 151.3, 200.9 and 251.8 g/kg carbohydrate levels, respectively. The results indicated that fish fed diets containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We also studied the effects of the change in the CHO/protein ratio as well as the inulin factors on immunity actors in intestinal mucosa and liver. Indeed, the presence of anti-nutritional factors in the diet can induce innate immune response of epithelial cells and in the liver [93][94][95]. In this study, a signi cant decrease of plasma nitric oxide (NO) in sh fed with the high-starch diet was also observed.…”
Section: Effects Of the Cho/protein Ratio And Inulin On The Immunolog...mentioning
confidence: 50%
See 1 more Smart Citation
“…We also studied the effects of the change in the CHO/protein ratio as well as the inulin factors on immunity actors in intestinal mucosa and liver. Indeed, the presence of anti-nutritional factors in the diet can induce innate immune response of epithelial cells and in the liver [93][94][95]. In this study, a signi cant decrease of plasma nitric oxide (NO) in sh fed with the high-starch diet was also observed.…”
Section: Effects Of the Cho/protein Ratio And Inulin On The Immunolog...mentioning
confidence: 50%
“…While the use of anti-nutritional factors can led to mucosal in ammation [94], a high-starch diet in rainbow trout may also result in higher production of liver pro-in ammatory cytokines [95], the liver in teleost being known to be involved in immune responses in teleosts [101,102]. Interestingly, here, high starch diets induced a signi cant decrease of the il1b, il8, and tnfa genes, suggesting that reducing of the proportion of plantproteins may result in a decrease of cytokines responses in the liver.…”
Section: Effects Of the Cho/protein Ratio And Inulin On The Immunolog...mentioning
confidence: 99%
“…We also studied the effects of the change in the CHO/protein ratio as well as the inulin factors on immunity actors in intestinal mucosa and liver. Indeed, the presence of anti-nutritional factors in the diet can induce innate immune response of epithelial cells and in the liver [ 93 95 ]. In this study, a significant decrease of plasma nitric oxide (NO) in fish fed with the high-starch diet was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of anti-nutritional factors can lead to mucosal inflammation [ 94 ], a high-starch diet in rainbow trout may also result in higher production of liver pro-inflammatory cytokines [ 95 ], the liver in teleost being known to be involved in immune responses in teleosts [ 98 , 99 ]. Interestingly, here, high starch diets induced a significant decrease of the il1b , il8 , and tnfa genes, suggesting that reducing of the proportion of plant-proteins may result in a decrease of cytokines responses in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The results of carbohydrate incorporation studies are largely controversial. One study has reported that the inoculation of more than 12.6%dietary carbohydrate reduces the growth performance of rainbow trout ( Oncorhynchus mykiss ) [ 7 ], whereas many other studies have demonstrated that a higher percentage of carbohydrates enhances the protein and energy retention in Siberian sturgeon ( Acipenser baerii ) [ 8 ] and O. mykiss [ 9 ]. Therefore, exogenous digestive enzyme supplementation in fish diets has garnered increasing attention in the aquaculture of Yangtze sturgeon ( A. dabryanus ) [ 10 ] and cachama ( Piaractus brachypomus ) [ 11 ] as it promotes carbohydrate digestion and assimilation in these fish.…”
Section: Introductionmentioning
confidence: 99%